2023
DOI: 10.1002/oby.23915
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood DNA methylation of immune and lipid metabolism genes is associated with maternal triglycerides and child adiposity

Stephanie W. Waldrop,
Sierra Niemiec,
Cheyret Wood
et al.

Abstract: ObjectiveFetal exposures may impact offspring epigenetic signatures and adiposity. The authors hypothesized that maternal metabolic traits associate with cord blood DNA methylation, which, in turn, associates with child adiposity.MethodsFasting serum was obtained in 588 pregnant women (27–34 weeks' gestation), and insulin, glucose, high‐density lipoprotein cholesterol, triglycerides, and free fatty acids were measured. Cord blood DNA methylation and child adiposity were measured at birth, 4–6 months, and 4–6 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Role of Epigenetic Programming in Immune Cells from Offspring Exposed to WSD Epigenetic changes due to maternal diet/obesity can occur throughout neonatal tissues and cells with lasting impact on neonatal development and beyond. Recent studies have shown that cord blood DNA methylation in neonates born to mothers with obesity correlated with maternal triglycerides and childhood adiposity [196]. In NHP studies, both HSPCs and bone marrow-derived macrophages (BMDM) from maternal WSD-exposed 3-year-old offspring were epigenetically modified to a more proinflammatory signature [6], despite weaning at 7 months to a normal chow diet.…”
Section: Mechanism Effect Referencesmentioning
confidence: 99%
“…Role of Epigenetic Programming in Immune Cells from Offspring Exposed to WSD Epigenetic changes due to maternal diet/obesity can occur throughout neonatal tissues and cells with lasting impact on neonatal development and beyond. Recent studies have shown that cord blood DNA methylation in neonates born to mothers with obesity correlated with maternal triglycerides and childhood adiposity [196]. In NHP studies, both HSPCs and bone marrow-derived macrophages (BMDM) from maternal WSD-exposed 3-year-old offspring were epigenetically modified to a more proinflammatory signature [6], despite weaning at 7 months to a normal chow diet.…”
Section: Mechanism Effect Referencesmentioning
confidence: 99%
“…CRC is among the disease that have been associated with metabolic programming [ 9 ]. Additionally, metabolic programming can affect epigenetic modifications, which can be influenced by various environmental factors, including nutrition [ 10 ]. Altered epigenetic patterns can regulate the expression of genes involved in cancer development and progression, including those related to cell cycle control, DNA repair, and apoptosi [ 11 ].…”
Section: Introductionmentioning
confidence: 99%